Desempenho de ativos tecnológicos sob influências macroeconômicas: Brasil, EUA e China (2019-2023) - Cogo, Vanessa dos Santos (My University, 2025)
In recent years, the technology sector has experienced exponential growth, driven by continuous innovations and changes in consumer behavior. This growth has had a significant impact on global financial markets, especially in the leading countries in the sector: the United States, China, and Brazil. However, the performance of technology- related financial assets can be influenced by various macroeconomic factors, such as interest rate fluctuations, exchange rate variations, and fiscal policies. Given this context, this study aims to analyze the behavior of technology assets in these three markets, focusing on macroeconomic influences between 2019 and 2023. The research follows a quantitative and applied approach with descriptive objectives. Through correlation analysis, t-Student test, and linear regression, it was possible to identify the relationships between macroeconomic factors and the performance of technology financial assets in Brazil, the United States, and China. Secondary data analysis was the primary technique adopted, using secondary data to investigate the specific characteristics and behaviors of technology financial markets in each country. The results indicate that the direct relationship between the American, Chinese, and Brazilian technology financial markets is more relevant than domestic macroeconomic factors. In practical terms, investors should consider market interdependence when making investment decisions in technology assets, particularly between emerging and developed markets. The research also paves the way for future investigations into the impact of regulatory changes and sustainability policies in the technology sector. [resumo fornecido pelo autor]
Nos últimos anos, o setor de tecnologia tem experimentado um crescimento exponencial, impulsionado por inovações contínuas e mudanças no comportamento do consumidor. Esse crescimento tem gerado um impacto significativo nos mercados financeiros globais, especialmente nos países líderes no setor: Estados Unidos, China e Brasil. O desempenho dos ativos financeiros relacionados à tecnologia, porém, pode ser influenciado por uma série de fatores macroeconômicos, como flutuações nas taxas de juros, variações cambiais e políticas fiscais. Diante disso, este estudo busca analisar o comportamento dos ativos de tecnologia nesses três mercados, focando nas influências macroeconômicas entre 2019 e 2023. A pesquisa foi realizada com uma abordagem quantitativa e natureza aplicada, com objetivos descritivos. Através de análise de correlação, teste t-Student e regressão linear, foi possível identificar as relações entre os fatores macroeconômicos e o desempenho dos ativos financeiros de tecnologia no Brasil, Estados Unidos e China. A análise de dados secundários foi a principal técnica adotada, utilizando dados secundários para investigar as particularidades e comportamentos dos mercados financeiros de tecnologia em cada país. Os resultados indicam que a relação direta entre os mercados financeiros tecnológicos americano, chinês e brasileiro é mais relevante do que os fatores macroeconômicos domésticos. Em termos de implicações práticas, os investidores devem considerar a interdependência dos mercados ao tomar decisões de investimento em ativos tecnológicos, especialmente entre os mercados emergentes e desenvolvidos. A pesquisa também abre caminho para futuras investigações sobre o impacto de mudanças regulatórias e políticas de sustentabilidade no setor de tecnologia. [resumo fornecido pelo autor]
Keywords: Administração financeira; Mercado financeiro - Brasil - Estados Unidos - China; Macroeconomia; Tecnologia; Investimentos; Financial administration; Money market - Brazil - United States - China; Macroeconomics; Technology; Investments